Effects of melatonin and oxytetracycline in autologous intraperitoneal ovary transplantation in rats - Sapmaz, E; Ayar, A; Celik, H; Sapmaz, T; Kilic, N; Yasar, MA (Maghira & Maas Publications, 2003)
OBJECTIVES: To comparatively investigate the effects melatonin and oxytetracycline as antioxidants on autologous intraperitoneal ovary transplantation in rats. SETTING AND DESIGN: 28 adult female Wistar rats with regular estrous cycles were randomly divided into four groups. Group 1 (n=7) was the control group; Group 2 (n=7) bilateral oophorectomy and intraperitoneal transplantation group; and Groups 3 (n=7) and 4 (n=7) firstly received 20 mg/kg/IP melatonin and 10 mg/kg/IP oxytetracycline., respectively and fifteen minutes after that, they had bilateral oophorectomy and intraperitoneal transplantation. Ovarian tissue and blood malondialdehyde (MDA) levels, superoxide dismutase (SOD) and glutathione peroxidase (GSHPx) levels were determined. Vaginal cytology and ovarian necrosis were histopathologically investigated. Kruskall Wallis analysis of variance was used in the statistical analysis of data. RESULTS: Ovarian necrosis, tissue MDA and plasma MDA levels were significantly higher in Group 2 compared to the Groups 1, 3 and 4 (p < 0.03). SOD and GSHPx levels were significantly lower in group 2 compared to the groups 1, 3 and 4 (p < 0.03). Melatonin was found to be more effective on ovarian necrosis and tissue MDA level than the use of oxytetracycline following autologous intraperitoneal ovary transplantation (p < 0.03). There was a significant positive correlation between tissue MDA level and ovarian necrosis and a very strong negative correlation between tissue MDA and SOD level (r(s) = +/-0.9, n=28, p=0.000). CONCLUSION: Although both melatonin and oxytetracycline were found to be effective in autologous intraperitoneal pelvic ovary transplantation, melatonin is more effective against both the ovarian necrosis and tissue MDA level in rats..
Keywords: melatonin; oxytetracycline; ovarian transplantation